Assistência técnica e extensão rural do Estado de Goiás: da aplicabilidade da legislação e de políticas efetivas - Marques, Rômulo César Barbosa (2017)
In Brazil and in Goiás there are numerous programs aimed at family agriculture, among them rural extension, with characteristics in its design and application that are problematic. This study shows that the problems are related to the lack of compliance with constitutional and legal determinations, lack of systemic concepts in the management of agricultural properties, as well as a lack of regional specialization that considers the knowledge of small rural producers and that can bring benefits to the chain Productive. What is perceived is a mistaken conception of such policies by starting from an erroneous conception of public function. And although it is a practical, enforcement and law-making observation, it has its best study, in a more detailed way, from the theoretical frameworks used, namely, Anthony Giddens, Ricardo Abramovay and Amartya Sen, with emphasis on the call Reflective modernity and development, based on economic, social, political and cultural concepts. After analyzing the policies of ATERs, we propose to present a policy currently employed in pilot projects by the state of Goiás, as a result of research and improvements for decades of activity of EMATER - GO - Technical Assistance and Rural Extension Company in Goiás. Results and how they have collaborated for a productive chain on a macroscopic scale is the ultimate goal to demonstrate that a new way of carrying out technical assistance and rural extension programs can and should be urgently implemented throughout the country as a development policy under the most Different aspects. Methodologically, the present research was based mainly on bibliographical readings of works and sites that bring elements related to the theme.